2011
DOI: 10.1016/j.neuroimage.2010.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain alterations associated with dyslexia predate reading onset

Abstract: Functional magnetic resonance imaging studies have reported reduced activation in parietotemporal and occipitotemporal areas in adults and children with developmental dyslexia compared to controls during reading and reading related tasks. These patterns of regionally reduced activation have been linked to behavioral impairments of reading-related processes (e.g., phonological skills and rapid automatized naming). The observed functional and behavioral differences in individuals with developmental dyslexia have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
179
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 211 publications
(209 citation statements)
references
References 75 publications
(126 reference statements)
25
179
0
5
Order By: Relevance
“…It has been hypothesized that hypoactivation in DD within left temporoparietal and occipitotemporal areas of the brain are fundamental to the language disorder itself, as differences in these areas during reading tasks are apparent, even when comparing children with DD to younger, typical readers, who are on the same reading level (44). Our results support this hypothesis and one can further hypothesize that prereading children at risk for DD exhibit reduced gray-matter volume indices in left temporoparietal and occipitotemporal brain regions (62), which then lead to a disruption of the network typically involved in phonological processing and subsequent reading failure. Brain regions, which were included in subsequent region of interest analyses, are shown in boldface.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It has been hypothesized that hypoactivation in DD within left temporoparietal and occipitotemporal areas of the brain are fundamental to the language disorder itself, as differences in these areas during reading tasks are apparent, even when comparing children with DD to younger, typical readers, who are on the same reading level (44). Our results support this hypothesis and one can further hypothesize that prereading children at risk for DD exhibit reduced gray-matter volume indices in left temporoparietal and occipitotemporal brain regions (62), which then lead to a disruption of the network typically involved in phonological processing and subsequent reading failure. Brain regions, which were included in subsequent region of interest analyses, are shown in boldface.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, reduced gray-matter volume indices in temporoparietal and occipitotemporal brain regions have been reported in prereading children at risk for DD compared with their peers (62). The left temporoparietal region of the brain is known to be crucial for the integration of letter and speech sounds (68) and has consistently demonstrated activation during phonological processing tasks in typically reading children and adults (for reviews, see refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding N1 (~170ms) ERP attenuation and its magneto-encephalographic homologue also point to diminished sensitivity to print in dyslexics (Helenius et al, 1999;Kronbichler et al, 2006;Maurer et al, 2007;. Furthermore, the following evidence points to the potential of occipito-temporal activity for predicting reading skills at a young age: i) structural alterations within the VWFS of at-risk children before school enrolment (Raschle et al, 2011); ii) its importance in learning to read supported by the early and rapidly emerging sensitivity to letters or letter strings (Brem et al, 2010;Cantlon et al, 2011); iii) the neurophysiological differences between normal readers and dyslexics seen in the corresponding N1 ERP (Maurer et al, 2007). Because interventions for poor readers might be most beneficial when started in parallel with reading acquisition (Bradley and Bryant, 1983) the identification of predictors at preschool age would be particularly valuable.…”
mentioning
confidence: 99%
“…An fMRI study by Specht and colleagues (Specht et al 2009) revealed a negative correlation of the strength of activation in the occipitotemporal cortex and the dyslexia risk index and a structural MRI study reported significantly reduced grey matter volume in the left occipito-temporal and bilateral parieto-temporal cortex, the left fusiform gyrus and the right lingual gyrus in familial at-risk children in preschool (Raschle et al, 2011). Interestingly, most areas with diminished grey matter volume in at-risk children, and especially the basal left occipito-temporal cortex often referred to as the visual word form system (VWFS) (Cohen et al, 2000;Vinckier et al, 2007), plays a key role in print processing when children learn to read (Brem et al, 2010;Maurer et al, 2006).…”
mentioning
confidence: 99%